2002
DOI: 10.1159/000063125
|View full text |Cite
|
Sign up to set email alerts
|

Histological Evaluation of Osteochondral Defects: Consideration of Animal Models with Emphasis on the Rabbit, Experimental Setup, Follow-Up and Applied Methods

Abstract: Regardless of their etiology, cartilage defects of articular joints remain one of the unsolved problems in medicine. Therefore, numerous techniques to enhance cartilage repair are under clinical or experimental investigation. In any serious approach experimental investigation should precede human application. If the decision is made to implement an animal model, which one should be used? What is a good experimental animal for osteochondral defects? Can chondral defects be evaluated? What is the critical size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 41 publications
0
50
0
2
Order By: Relevance
“…The adult rabbit calvarial "critical size defect" model was chosen because the cranial bones, like the maxilla and mandible, are formed through intramembranous ossification 32,33 . This model has been extensively investigated and characterized with regards to its intrinsic bone healing capacity 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The adult rabbit calvarial "critical size defect" model was chosen because the cranial bones, like the maxilla and mandible, are formed through intramembranous ossification 32,33 . This model has been extensively investigated and characterized with regards to its intrinsic bone healing capacity 34 .…”
Section: Discussionmentioning
confidence: 99%
“…*p < 0.05, **p < 0.01. inbreeding, it is the most representative and justifiable experimental animal model for use in cartilage research. 26 Rudert have reported that success in repair of a 3-mm-diameter defect in the trochlea does not offer any benefit, since, according to the literature, perfect healing has never been observed, even with common 3-mm-diameter defects. 26 Although spontaneous regeneration of cartilage was observed to some extent in the defect-only group, the quality of the regenerated cartilage was poor and contained a considerable amount of fibrotic tissue on the surface, even 3 months after implantation.…”
Section: Fig 4 Gross Findings Of the Cartilage Defect With Implantsmentioning
confidence: 99%
“…26 Rudert have reported that success in repair of a 3-mm-diameter defect in the trochlea does not offer any benefit, since, according to the literature, perfect healing has never been observed, even with common 3-mm-diameter defects. 26 Although spontaneous regeneration of cartilage was observed to some extent in the defect-only group, the quality of the regenerated cartilage was poor and contained a considerable amount of fibrotic tissue on the surface, even 3 months after implantation. Formation of this type of fibrocartilage might be attributable to bone marrow stem cells and growth factors that originated from subchondral bone.…”
Section: Fig 4 Gross Findings Of the Cartilage Defect With Implantsmentioning
confidence: 99%
“…42 Investigation of earlier time points in the process can yield insight into mechanisms of early tissue fill, as well as alert to potential delays in healing. In the current study, MRI morphologic analysis showed no differences in defect fill at either time point, indicative of comparable healing of the TP-508 tissues compared to controls at this structural level.…”
Section: Evaluation Of Osteochondral Defect Repairmentioning
confidence: 99%